2018
DOI: 10.14311/nnw.2018.28.025
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Retinal Abnormalities Using Machine Learning Methodologies

Abstract: This paper presents an algorithm for the design of a computer aided diagnosis system to detect, quantify and classify the lesions of non-proliferative diabetic retinopathy as well as dry age related macular degeneration from the fundus retina images. Symptoms of non-proliferative diabetic retinopathy in images consist of bright lesions like hard exudates, cotton wool spots and dark lesions like microaneurysms, hemorrhages. Dry age related macular degeneration is manifested as a bright lesion called drusen. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…This comparative analysis of the proposed lesion detection approach with existing techniques reveals that it outperforms other state-of-the-art methods, with the greatest accuracy improvement of 5.90% over Nayak et al [29]. Comparison with other techniques shows accuracy improvement of 3.52%, 2.90% and 3.77% over Priya et al [30], Paing et al [31] and Saha et al [32] respectively.…”
Section: Discussionmentioning
confidence: 78%
“…This comparative analysis of the proposed lesion detection approach with existing techniques reveals that it outperforms other state-of-the-art methods, with the greatest accuracy improvement of 5.90% over Nayak et al [29]. Comparison with other techniques shows accuracy improvement of 3.52%, 2.90% and 3.77% over Priya et al [30], Paing et al [31] and Saha et al [32] respectively.…”
Section: Discussionmentioning
confidence: 78%
“…The decision tree has been expanded in Figs. 4 [30,31]. In the current paper, we have included KNN classifier.…”
Section: Discussionmentioning
confidence: 99%
“…It is robust to larger databases [25]. Machine learning using Single Layer Perceptron (SLP) algorithm has also been tested and its performance is compared with SVM and NB classifier [31]. It was concluded that SLP and SVM give comparable results and both outperform NB classifier.…”
Section: Introductionmentioning
confidence: 99%
“…SVM works by finding the best hyperplane for dividing two different data classes ∈ −1,1 . The best hyperplane can be formulated in Equation (1) [38].…”
Section: B Support Vector Machine (Svm)mentioning
confidence: 99%